Sex and seasonal differences in hippocampal volume and neurogenesis in brood‐parasitic brown‐headed cowbirds (Molothrus ater). Issue 11 (11th August 2016) - Guigueno, Mélanie F.; MacDougall‐Shackleton, Scott A.; Sherry, David F.
ABSTRACT: Brown‐headed cowbirds ( Molothrus ater ) are one of few species in which females show more complex space use than males. Female cowbirds search for, revisit, and parasitize host nests and, in a previous study, outperformed males on an open field spatial search task. Previous research reported a female‐biased sex difference in the volume of the hippocampus, a region of the brain involved in spatial memory. Neurons produced by adult neurogenesis may be involved in the formation of new memories and replace older neurons that could cause interference in memory. We tested for sex and seasonal differences in hippocampal volume and neurogenesis of brood‐parasitic brown‐headed cowbirds and the closely related non‐brood‐parasitic red‐winged blackbird ( Agelaius phoeniceus ) to determine whether there were differences in the hippocampus that reflected space use in the wild. Females had a larger hippocampus than males in both species, but hippocampal neurogenesis, measured by doublecortin immunoreactivity (DCX+), was greater in female than in male cowbirds in the absence of any sex difference in blackbirds, supporting the hypothesis of hippocampal specialization in female cowbirds. Cowbirds of both sexes had a larger hippocampus with greater hippocampal DCX+ than blackbirds. Hippocampus volume remained stable between breeding conditions, but DCX+ was greater post‐breeding, indicating that old memories may be lost through hippocampal reorganization following breeding. Our results support, in part, the hypothesis that the hippocampus of cowbirds is specialized for brood parasitism. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1275–1290, 2016